Stunting Reduction Policy: Learning From the Field - Dasuki, Niken Paramarti; Sukarso, Sukarso; Rofik, Ahmad (Technium Social Sciences Journal, 2024)
Stunting is a condition of growth failure in toddlers (babies under five years old) as a result of chronic malnutrition so that the child is too short for his age. This study was located in Banyumas Regency. The selection of the location of this study in Sumbang District, namely Datar Village, Karangturi Village, Susukan Village and Gandatapa Village because these villages are the priority for the acceleration of integrated stunting reduction in Banyumas Regency. This study aims to reveal and describe the community’s interpretation of stunting and community expectations with the existence of stunting policies in villages affected by the integrated stunting reduction acceleration priority program. This study uses a qualitative method with a descriptive approach targeting heads of families who have toddlers (under 5 years old). The data collection method uses in-depth interviews, observations and focus group discussions. The results of this study indicate that there is an understanding of stunting prevention that is not yet fully good in all elements in the village community concerned. Only cadres and village officials have a relatively good understanding, which tends to be normative and administrative, about the stunting prevention program in their respective villages. This study also produces recommendations or implications for the need for a nutrition awareness movement in all elements of the village community (inclusiveness) concerned. This movement shows that there is no dependence on the government to fulfill the nutritional needs of rural families